Yeast β-Glucan Altered Intestinal Microbiome and Metabolome in Older Hens - Zhen, Wenrui; Liu, Yuchen; Shao, Yujing; Ma, Yanbo; Wu, Yuanyuan; Guo, Fangshen; Abbas, Waseem; Guo, Yuming; Wang, Zhong (Frontiers in Microbiology, 2021)
The prebiotics and probiotics mediated positive modulation of the gut microbiota composition is considered a useful approach to improve gut health and food safety in chickens. This study explored the effects of yeast β-glucan (YG) supplementation on intestinal microbiome and metabolites profiles as well as mucosal immunity in older hens. A total of 256 43-week-old hens were randomly assigned to two treatments, with 0 and 200 mg/kg of YG. Results revealed YG-induced downregulation of TLRs and cytokine gene expression in the ileum without any effect on the intestinal barrier. 16S rRNA analysis claimed that YG altered α-and β-diversity and enriched relative abundance of class Bacilli, order of Lactobacillales and Enterobacteriales, family of Lactobacillaceae and Enterobacteriaceae, genus of Lactobacillus and Escherichia-Shigella, species uncultured-bacterium-Lactobacillus. Significant downregulation of cutin, suberine and wax biosynthesis, atrazine degradation, vitamin B6 metabolism, phosphotransferase system, steroid degradation, biosynthesis of unsaturated fatty acids, aminobenzoate degradation and quorum sensing, whereas upregulation of ascorbate and aldarate metabolism, C5-Branched dibasic acid metabolism, glyoxylate and dicarboxylate metabolism, pentose and glucuronate interconversions, steroid biosynthesis, carotenoid biosynthesis, porphyrin and chlorophyll metabolism, sesquiterpenoid and triterpenoid biosynthesis, lysine degradation, and ubiquinone and other terpenoid-quinone biosynthesis were observed in YG-treated hens, as substantiated by the findings of untargeted metabolomics analysis. Overall, yeast β-glucan manifests prebiotic properties by altering gut microbiome and metabolites profiles and can downregulate intestinal mucosal immune response of breeder hens.